2016
DOI: 10.1016/j.lindif.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' depressive symptoms and parent-report of child executive function among young children in Uganda

Abstract: Maternal mental health (particularly depression) may influence how they report on their child’s behavior. Few research studies have focused on Sub-Saharan countries where pediatric HIV concentrates and impacts child neuropsychological development and caregiver mental health. We investigated the associations between caregivers’ depressive symptoms and neuropsychological outcomes in HIV-infected (n=118) and HIV-exposed (n=164) Ugandan children aged 2–5 years. We compared performance-based tests of development (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
4
16
3
Order By: Relevance
“…. No association was found between caregiver depression and developmental outcomes in our study, although such associations have been observed in earlier studies .…”
Section: Discussioncontrasting
confidence: 69%
“…. No association was found between caregiver depression and developmental outcomes in our study, although such associations have been observed in earlier studies .…”
Section: Discussioncontrasting
confidence: 69%
“…We demonstrate that PHIV status itself was associated with poor child-wellbeing only in caregiving environments characterized by high levels of caregiver stress. This observation confirms the benefit of effective HIV care for PHIV but also highlights opportunities for adjunct interventions to sustain the benefit of excellent HIV care by enhancing the capacity of HIV-affected households to cope with psychosocial adversity including caregiver depression (Familiar et al, 2016) related to their HIV-affected status. On the one hand, PHIV were similar to uninfected children in most QOL measures, with possible higher general vitality than uninfected peers, but only in low caregiver stress environments.…”
Section: Discussionsupporting
confidence: 65%
“…In Uganda, the prevalence of HIV was 7.6% among women ages 15 to 64 in 2017 (PHIA Project, ). Adverse effects of caregiver mental health problems on parenting, child health, and caregiver reporting of child development outcomes have been described among female HIV‐affected Ugandan caregivers (i.e., a child's primary caregiver who may or may not be the biological parent) (Familiar, Murray, et al., ; Familiar, Nakasujja, et al., ; Murray et al., ). Parenting self‐efficacy, which also affects parent–child interaction, has received far less attention.…”
Section: Introductionmentioning
confidence: 99%